Pengaruh Influencer, Brand Image, dan Product Quality, Terhadap Keputusan Pembelian Sepatu Compass di Purwokerto - Setiono, Laras Alif; Astuti, Herni Justiana; Septin Muji R., Tri; Yusnar Kharismasyah, Alfato (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to analyze the influence of influencers on Instagram social media, brand image, and product quality on purchasing decisions for Compass shoes among the people of Purwokerto. This research is a type of quantitative research with a research sample of 146 respondents who live in Purwokerto. The sampling method used is. Purposive Sampling, namely selecting respondents who are willing and meet the specified sample criteria. For data analysis, the Structural Equation Modeling (SEM) method was used with the Smart PLS version 4.0 tool. The tests carried out include the outer model test to assess the validity and reliability of the construct, the inner model test to evaluate the relationship between latent variables, and hypothesis testing to test the significance of the influence of each independent variable on the dependent variable. The research results show that partially the brand image and product quality are proven to have a positive and significant influence on the decision to purchase Compass shoes. On the other hand, influencers do not have a significant influence on the decision to purchase Compass shoes. These findings show that brand image and product quality factors are more dominant in influencing purchasing decisions than the influence of influencers on Instagram.